1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Triangle line integral

  1. May 3, 2009 #1
    Let C be the triangle in the plane from (0,0) to (1,1) to (0,1) back to (0,0). evaluate the line integral of f along C if f(x,y)=(x+2y).

    C1: x=t y=t ds=root(1)dt, integrated t+2t from 0 to 1 to get 3/2
    C2: x=-t ds=root(1)dt, integrated -t from -1 to 0 to get 1/2
    C3: y=-t, ds=root(1)dt integrated -2t from -1 to 0 to get 1.
    added up 3/2, 1/2, and 1 to get the wrong answer.
    the correct answer is (1/2)(3root2 + 7)

    looks like im parametizing completely wrong. so how do i go about this? thanks.
  2. jcsd
  3. May 3, 2009 #2


    User Avatar
    Homework Helper

    For starters regarding path C1, c'(t)=(1,1). What is the length of the vector (1,1)? The rest of C1 is correct.

    For path C2 c(1) should yield (1,1). In your case c(1)=(1,k), with k an undetermined parameter since you didn't parametrize y for this side of the triangle.

    For path C3 a similar problem occurs.

    You want to find yourself a parametrization of the following form:

    [tex]c(t) = \left\{ \begin{matrix} (t,t) & 0 \leq t \leq 1 \\ (..,..) & 1 \leq t \leq 2 \\ (..,..) & 2 \leq t \leq 3 \end{matrix} \right[/tex]

    What you have been doing so far is making some weird jumps in time for your C2 and C3 paths. I suggest you draw the triangle and seeing as all sides are straight lines use y=at+b to parametrize each segment.

    Example for the side (1,1)->(0,1)

    We know that the y coordinate remains constant and equals 1. Therefore our parametrization will be of the form (x(t),1). We now need to find x(t). x(t) decreases linearly between 1 and 0 so its equation will look like x=at+b. For t=1 we know that x=1 therefore 1=a+b. For t=2 we know that x=0 therefore 0=2a+b. Solving for a and b will yield x(t)=2-t therefore c(t)=(2-t,1).
    Last edited: May 3, 2009
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook